OPTIMALISASI PENGEMBANGAN PUPUK ORGANIK UNTUK MENINGKATKAN PRODUKSI TANAMAN HIDROPONIK PADA KELOMPOK PKK DESA SUKAMAKMUR SEBAGAI UPAYA KETAHANAN PANGAN - Ulul Hidayah; Ariyanti Hartari; Pepi Rospina Pertiwi; Nurul Nisa'a Amin; Dewi Juliah Ratnaningsih; Restu Para Ratu; Nindyarahmah Isabillah (Jurnal AbdiMas Nusa Mandiri, 2026)
The high dependence on commercial chemical fertilizers (AB Mix) in hydroponic cultivation has become a major challenge for the Family Welfare Movement (PKK) group in Sukamakmur Village, Ciomas District, Bogor Regency, resulting in high production costs. At the same time, the area generates abundant household organic waste that remains underutilized. This Community Service (PkM) program at the Open University aims to provide technical assistance and technology transfer in waste decomposition to reduce agricultural input costs while increasing the productivity of hydroponic vegetables in a independent and sustainable way. The program employed a participatory approach consisting of three stages: preparation, including coordination with the PKK group, household waste assessment, training material development, and procurement of equipment and materials; implementation, involving hands-on training on controlled anaerobic Liquid Organic Fertilizer (POC) production and composting for leachate extraction; and evaluation through observations of participants' ability to apply the acquired knowledge, pre-test and post-test questionnaires, and participant satisfaction surveys. The program significantly improved participants' capacity and farming efficiency. Average cognitive scores increased by 13.26% for POC production and 18.92% for composting techniques. Participants reported very high satisfaction, and the PKK group successfully produced high-quality organic fertilizers independently, providing a chemical residue-free nutrient alternative for hydroponic vegetables while reducing household organic waste generation.